Peran Administrasi Kesiswaan Untuk Kemajuan Pendidikan di Sekolah - Nuralia Nuralia; Miftahir Rizqa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
. In a school there are teachers or educators, learners or students, and other education personnel. The most important thing in school is the existence of students, where without students a teacher cannot teach a science because students are the object of learning. students in education must be able to get their rights and obligations as a student. In schools, education administration is very important because it can make rules, guidance and control over the rules that apply at school. Good student management can improve the knowledge, skills, and attitudes of students.